Selecting the Low Alloy-Tempered Steel for Manufacturing the Highly Loaded Responsible Parts - Lazic, Vukic; Arsic, Dusan; Nikolic, Ruzica R.; Arsic, Miodrag; Hadzima, Branislav (Communications - Scientific letters of the University of Zilina, 2017)
The selecting procedure of the optimal material for manufacturing the highly loaded responsible parts for military applications is presented in this paper. The considered part is in exploitation subjected to complex compressive-impact loading and cyclically to high temperatures, as well. The proper selection of material can be done exclusively based on the theoretical and experimental analysis of properties of the steel in question. The theoretical and experimental selecting of adequate steel for manufacturing such parts is done based on requirements arising from their working conditions. Based on the available data for various steels, chemical composition, mechanical and technological properties, available CCT diagram, the optimal steel was selected for the given working conditions. After the selection of the material, experimental investigations on specially prepared material samples were conducted. The real chemical composition of material was established, its most important mechanical properties were determined, the hardness was measured and the microstructure was determined, as well. After the conducted theoretical and experimental investigations, the responsible machine part was manufactured from the selected material by forging. Then, the mechanical and heat processing was executed, after which the part was tested in the real working conditions. Based on investigations of part’s behavior in the real working conditions, it was concluded that the selection of the material was adequate.